Genetic landscape of pediatric acute liver failure of indeterminate origin - Lenz, Dominic; Schlieben, Lea D.; Shimura, Masaru; Bianzano, Alyssa; Smirnov, Dmitrii; Kopajtich, Robert; Berutti, Riccardo; Adam, Rüdiger; Aldrian, Denise; Baric, Ivo; Baumann, Ulrich; Bozbulut, Neslihan E.; et al. (Hepatology, 2024)
Background and Aims: - Pediatric acute liver failure (PALF) is a life-threatening condition. In Europe, the main causes are viral infections (12%-16%) and inherited metabolic diseases (14%-28%). Yet, in up to 50% of cases the underlying etiology remains elusive, challenging clinical management, including liver transplantation. We systematically studied indeterminate PALF cases referred for genetic evaluation by whole-exome sequencing (WES), and analyzed phenotypic and biochemical markers, and the diagnostic yield of WES in this condition. - Approach and Results: - With this international, multicenter observational study, patients (0-18 y) with indeterminate PALF were analyzed by WES. Data on the clinical and biochemical phenotype were retrieved and systematically analyzed. - Results: - In total, 260 indeterminate PALF patients from 19 countries were recruited between 2011 and 2022, of whom 59 had recurrent PALF. WES established a genetic diagnosis in 37% of cases (97/260). Diagnostic yield was highest in children with PALF in the first year of life (41%), and in children with recurrent acute liver failure (64%). Thirty-six distinct disease genes were identified. Defects in NBAS (n=20), MPV17 (n=8), and DGUOK (n=7) were the most frequent findings. When categorizing, the most frequent were mitochondrial diseases (45%), disorders of vesicular trafficking (28%), and cytosolic aminoacyl-tRNA synthetase deficiencies (10%). One-third of patients had a fatal outcome. Fifty-six patients received liver transplantation. - Conclusions: - This study elucidates a large contribution of genetic causes in PALF of indeterminate origin with an increasing spectrum of disease entities. The high proportion of diagnosed cases and potential treatment implications argue for exome or in future rapid genome sequencing in PALF diagnostics.
Gesehen am 07.08.2024